Sappo: Sulapa Eppa Walasuji as the Ideas of Creation Three Dimensional Painting - Hasbi Hasbi (Pascasarjana Institut Seni Indonesia Surakarta, 2021)
Lontara is a traditional script of the Bugis-Makassar community, derived from the word lontar, a type of plant in South Sulawesi, which is still used and maintained. Sappo (Bugis): fence used to limit (surround, insulate) land and houses. The Bugis-Makassar community as a whole always has a Sappo / fence to protect themselves, their families, and their nation. Sulapa eppa (four sides) is a mystical form of classical Bugis-Makassar belief that symbolizes the universe’s composition, wind-fire-water-earth. Walasuji is a kind of bamboo fence in a rhombic ritual. Walasuji comes from the word wala, which means separator/fence/guard, and suji means daughter (metaphor of something of value, which must be under protection). The research aims to create three-dimensional paintings with the idea of creation, Sappo: Sulapa eppa walasuji. The symbolic expression concept borrows the Lontara tradition’s idioms, making works of metaphorical Sappo (montage) titles; Posi’ Symbolic expressions are used as research methods to create works. Researchers borrow traditional idioms as a place of expression. Symbolic abstraction works are conceptually a form of modern art by utilizing the Lontara tradition's idiom as a basic element of preparing the work. The contextual use of idioms is no longer intact because there is a degradation in the artists’ processing when interpreting symbolic forms. The expression of tradition is no longer a thematic pouring of ideas, still, as a textual symbol offered by artists to provide freedom of interpretation, Sappo: Sulapa eppa walasuji as the idea of creating paintings. The results of the study explore the elements of form and express the message conveyed through the work of three-dimensional images with the concept of creation, Sappo: Sulapa eppa walasuji, a work of metaphorical painting Sappo (montage) title: Posi, which is essentially God, as the protector of everything from the whole Sappo metaphor. Sappo, an idiom of tradition, is portrayed as a form of the symbolism of reflections on researchers’ lives visualized in the entire artwork. The visual elements used, stone, wood, bamboo, and paint, are at the same time a metaphor for the universe, which is God’s creation.